Magnesium ion-dependent triple-helix structure formed by homopurine-homopyrimidine sequences in supercoiled plasmid DNA. - Kohwi, Y (1988)
DNA can be chemically cleaved at the site of chloroacetaldehyde-modified residues by the chemicals used for Maxam-Gilbert sequencing reactions. Use of this technique facilitates fine structural analysis of unpaired DNA bases in DNA with non-B-DNA structure. This method was used to study the non-B-DNA structure adopted by the poly-(dG).poly(dC) sequence under torsional stress at various ionic conditions. In the presence of 2 mM Mg2+, the 5' half of the deoxycytosine tract is very reactive to chloroacetaldehyde, while the 3' half is virtually unreactive. In the poly(dG) tract, chloroacetaldehyde reaction is restricted to the center guanine residues. In the absence of Mg2+, however, it is the 5' half of the deoxyguanine tract that is reactive to chloroacetaldehyde, while the 3' half is unreactive. And chloroacetaldehyde reaction is restricted to the center cytosine residues in the poly(dC) stretch. These results strongly suggest that the poly(dG).poly(dC) sequence is folded into halves from the center of the sequence to form a tetra-stranded-like structure. Such a structure contains either a triplex consisting of poly(dG).poly(dG).poly(dC) strands in the presence of Mg2+ or a triplex consisting of poly(dC).poly(dG).poly(dC) strands in the absence of Mg2+. The fourth strand, not involved in triplex formation, is closely associated with the triplex and is positioned in such a way that DNA bases are exposed and freely accessible to the chloroacetaldehyde reaction.